2012
DOI: 10.1021/jp210577t
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Properties of Hexane in Pseudomorphic MCM-41 Mesoporous Silicas Explored by Pulsed Field Gradient NMR

Abstract: International audiencePulsed field gradient (PFG) NMR is a powerful tool to examine diffusion of adsorbates in porous systems. The use of mesoporous silicas with uniform particle sizes allowed us to demonstrate the possibilities of this technique. In particular, we confirmed that, in the Mitra mathematical approach of diffusion, the surfaceto-volume ratio is related to the geometry of the whole particle and not of a single pore. Hexane diffusion measured by PFG-NMR was efficient to study innovative materials l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…The potential of this type of porous materials has been impressively demonstrated in ref. [13,25,26] Herein, we present the first results of a systematic PFG NMR diffusion study in assemblies of mesoporous FAU-type zeolite nanosheets. PFG NMR diffusion measurements of guest molecules in this material are complicated, however, by their relatively short nuclear magnetic relaxation time in the medium-pore-size MFI zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of this type of porous materials has been impressively demonstrated in ref. [13,25,26] Herein, we present the first results of a systematic PFG NMR diffusion study in assemblies of mesoporous FAU-type zeolite nanosheets. PFG NMR diffusion measurements of guest molecules in this material are complicated, however, by their relatively short nuclear magnetic relaxation time in the medium-pore-size MFI zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that for monomodal porosities the diffusivities increases when the pore size increases: pore diameters of 3.8 nm,6.0 nm, and 18 nm lead to diffusion coefficients of 4.1 Â10 À10 m 2 s À1 , 5.9 Â 10 À10 m 2 s À1 , and 50 Â 10 À10 m 2 s À1 , respectively. The greater values of diffusivities obtained in the work of Adem et al [55] was probably due to the smaller molecular size of hexane compared to the molecular size of probe molecules used in the present work. With the increase in the molecular size, less and less probe molecules can enter the micropores which yields a more mesopore controlled process and a lower activation energy.…”
Section: Solvent Uptake and Apparent Diffusivitiesmentioning
confidence: 52%
“…In addition to that, the diffusion in small mesopores plays an important role. Adem et al [55] studied diffusion properties of hexane in pseudomorphic MCM-41 mesoporous silicas by Pulsed Field Gradient (PFG) NMR. The study of silicas with different particle sizes and different pore sizes and their MCM-41 pseudomorphs as a function of time allowed to demonstrate the possibilities of this technique.…”
Section: Solvent Uptake and Apparent Diffusivitiesmentioning
confidence: 99%
“…Different degrees of transformation were obtained not, as reported in most of the earlier work, e.g., in [24], by interrupting the synthesis after different synthesis durations, but by using different volumes of the CTAOH solution per unit mass of the initial silica gel. Thus, the transformation stopped when the CTAOH supplied for dissolution of the initial silica gel and “re-precipitation” of the MCM-41 product was consumed.…”
Section: Resultsmentioning
confidence: 96%